Intercultural Communication: Strategy to Improve School Competitiveness Based on Public Demand - Zamroni Zamroni; Hasan Baharun; Fathor Rozi; Wahidatus Sholeha; Yuliana Anggraini (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Having a strategy to increase the institution's competitiveness provides positive energy for an institution to develop the institution. This study analyzes and examines strategies to increase competitiveness through public demand intermediaries at RA Masyitoh III Sumberanyar Paiton Probolinggo. This research uses a qualitative approach. Technical analysis of the data through interviews, observation, and documentation is then carried out reduction which is processed on the display of the last data drawing conclusions. Research shows results; the strategy of increasing the competitiveness of public demand in RA Masyitoh III is carried out by creating school branding, public engagement, and continuous improvement through evaluation of the implementation of school branding and public engagement that has been running. From the study results, the public demand strategy carried out by RA Masyithoh III became a breakthrough for institutions at the level in the Paiton region that do not have a marketing strategy. The implications for the institution are that the institution is increasingly recognized by the broader community with increasingly highlighted characteristics. The implications for teachers are that teachers will further increase their competence in their respective fields to keep up with the institution's development.